1979
DOI: 10.1136/jnnp.42.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Uraemic myoclonus: an example of reticular reflex myoclonus?

Abstract: S U M M A R Y Two patients are described who developed action, reflex myoclonus during acute renal failure. In both cases the myoclonus was abolished after the intravenous administration of clonazepam. We suggest that the characteristic action myoclonus, which occurs in both acute renal failure and postanoxic encephalopathy, is caused by a disturbance of function in the lower brainstem reticular formation.A number of abnormal movements may occur in patients with acute renal failure. These include muscle fascic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 7 publications
0
12
1
Order By: Relevance
“…If symptomatic treatment is warranted, clonazepam is reported to be effective. If a dramatic response is needed, clonazepam may be given intravenously with appropriate precautions taken to monitor and support vital signs if needed [16]. 5-Hydroxytryptophan was initially reported as helpful, but is now used rarely, if at all [61].…”
Section: Reticular Reflex Myoclonusmentioning
confidence: 99%
See 1 more Smart Citation
“…If symptomatic treatment is warranted, clonazepam is reported to be effective. If a dramatic response is needed, clonazepam may be given intravenously with appropriate precautions taken to monitor and support vital signs if needed [16]. 5-Hydroxytryptophan was initially reported as helpful, but is now used rarely, if at all [61].…”
Section: Reticular Reflex Myoclonusmentioning
confidence: 99%
“…This designation does not include segmental myoclonus generation as the pathophysiology and characteristics of segmental myoclonus are distinct. Some examples of subcortical-nonsegmental myoclonus with their putative source locations in parentheses are: myoclonusdystonia syndrome (basal ganglia), opsoclonus-myoclonus syndrome (brainstem-cerebellar circuits), reticular reflex myoclonus (brainstem reticular formation), and propriospinal myoclonus (spinal cord) [14][15][16].…”
Section: Subcortical-nonsegmental Myoclonusmentioning
confidence: 99%
“…Brainstem reticular reflex myoclonus has been reported most frequently in patients with generalised cerebral insults (hypoxia2, 6 and renal failure3) and only occasionally in patients with localised disease (cervical trauma8). It is known to coexist with cortical myoclonus 9.…”
Section: Discussionmentioning
confidence: 99%
“…The sudden, generalised, shock‐like, involuntary movements that characterise reticular reflex myoclonus are said to originate in the lower brainstem 1. It was described initially in the setting of chronic post‐hypoxic myoclonus,2 and subsequently in renal failure,3 non‐dopa‐responsive parkinsonism,4 Lyme disease,5 and procarbazine therapy for Hodgkin disease 5. These generalised cerebral conditions rarely cause discrete brainstem pathology that can be implicated clearly in the development of this movement disorder.…”
mentioning
confidence: 99%
“…Patients with renal failure exhibit a variety of sensory-motor disorders, myoclonus [477] and restless legs syndrome [73,395,501,504]. Chadwick and French [59] reported that uremic myoclonus closely resembles posthypoxic myoclonus. They suggested that uremic myoclonus may be caused by the dysfunction of the NGC/NMC.…”
Section: Myoclonus (Including Restless Legs Syndrome and Periodic Legmentioning
confidence: 98%